Peran Asosiasi Penyelenggara Jasa Internet Indonesia (APJII) Sumatera Utara dalam Mensosialisasikan Keamanan Berinternet kepada Masyarakat menurut Perspektif Komunikasi Islam - Nurul Adha Almayora Nasution (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2024)
forms of socialization of APJII North Sumatra in socializing internet security and to determine the obstacles and solutions of APJII North Sumatra in socializing internet security. The method used in this study is a qualitative method with a Communication Science approach (Diffusion of Innovation). Because this study explains the phenomena that occur in the field by collecting data obtained from research informants. The results of the study found by the researcher are as follows, basically the role of the Indonesian Internet Service Providers Association (APJII) of North Sumatra refers to the Regulation of the Minister of Communication and Information of the Republic of Indonesia Number 32 of 2015 contained in article 2, namely: creating order in the management of Internet Protocol Numbers (PI), protecting the public interest from misuse and risk of loss due to management and use of PI Numbers that are not in accordance with the provisions of laws and regulations and providing a sense of security, justice and legal certainty for internet managers and users. The Socialization Programs delivered are public dialogue, press conferences, socialization carried out through the Miss Internet Indonesia program, etc. Forms of APJII North Sumatra Socialization in socializing internet security to the community according to the Islamic Communication Perspective are external socialization and internal socialization. The obstacles experienced by APJII North Sumatra are human resources that are still low because there are still many people who are not media literate and lack of time between APJII North Sumatra members, etc. Implicitly, all solutions provided by APJII North Sumatra are for the good of the community, in this case related to the elements of da'wah, namely amar makruf nahi mungkar and the principle of reward and sin is the provision of motivation and conveying good things. So from the data obtained by the researcher, the role of the Indonesian Internet Service Provider Association (APJII) North Sumatra has not been maximized. This can be seen from the fact that there are still many people who are not information literate with the socialization of internet security carried out by APJII North Sumatra.